Iron-based sintered sliding member and its manufacturing method
The iron-based sintered sliding member addresses environmental concerns and cost issues by incorporating dispersed sulfide particles and pores, enhancing sliding performance and wear resistance through controlled sintering.
Patent Information
- Application Number
- JP2023199937
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-08-29
- Filing Date
- 2023-11-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2039-08-28
AI Technical Summary
Existing iron-based sintered sliding members face challenges in reducing lead content for environmental reasons and improving friction and wear resistance, while copper-based sintered bodies are costly and require further enhancements.
An iron-based sintered sliding member with dispersed sulfide particles containing Cr, Ca, V, Ti, or Mg, and pores, sintered at 900°C to 1200°C, to achieve a high area ratio and number of fine sulfide particles for improved sliding performance.
The solution provides an iron-based sintered sliding member with enhanced sliding performance and reduced wear, utilizing fine sulfide particles and pores for improved lubrication and strength.
Smart Images

Figure 0007601193000006 
Figure 0007601193000007 
Figure 0007601193000008
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to an iron-based sintered sliding member and a method for producing the same. [Background technology]
[0002] The so-called powder metallurgy method, in which raw material powder is compressed in a die and the resulting green compact is sintered, is economically advantageous because it can be shaped into a near-net shape, which means less material loss due to subsequent machining and because products of the same shape can be mass-produced once a die is made. Powder metallurgy also allows for a wide range of alloy design, as it can produce special alloys that cannot be obtained by alloys produced by normal melting. For this reason, it is widely used in mechanical parts, including automobile parts.
[0003] Among mechanical parts, it is important for sliding members to have a low friction coefficient and wear resistance. In particular, in applications where high surface pressure is applied, sliding members formed of copper-based sintered bodies such as bronze-based and lead bronze-based are preferably used. Conventional copper-based sintered bodies can improve their wear resistance because the pores in the sintered body retain lubricating oil, whereas lead bronze-based sintered bodies can improve their wear resistance because the lead phase in the matrix acts as a solid lubricant.
[0004] Patent Document 1 proposes an iron-based sintered sliding member having excellent sliding properties and mechanical strength, the iron-based sintered sliding member having a metal structure consisting of a ferrite matrix in which sulfide particles are dispersed and pores, in which the sulfide particles are dispersed at 15 to 30 volume % relative to the matrix. Patent Document 1 describes that the sulfides precipitated in the matrix preferably have a certain size in order to exert a solid lubricating effect. Specifically, Patent Document 1 proposes that the area of sulfide particles with a maximum particle size of 10 μm or more preferably occupies 30% or more of the area of the entire sulfide particles. Patent Document 2 proposes a machinable sintered component in which MnS particles of 10 μm or less are uniformly dispersed within crystal grains over the entire surface of the matrix structure, as a sintered component that improves machinability while maintaining strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-181381 A [Patent Document 2] JP 2002-332552 A Summary of the Invention [Problem to be solved by the invention]
[0006] Lead-bronze sintered bodies contain a large amount of lead, so in order to address environmental issues, it is desirable to reduce the amount of lead and develop alternative materials. Various materials are being considered as alternative materials to lead-bronze sintered bodies, but further improvements in the friction coefficient and wear resistance of copper-based sintered bodies are desired. In addition, copper-based sintered bodies have a problem of high costs due to the large amount of copper used.
[0007] From the description in Patent Document 1, in an iron-based sintered sliding member, the particle size of the sulfide particles in the matrix is preferably as large as 10 μm or more from the viewpoint of sliding performance. In Patent Document 1, iron sulfide is added to iron powder containing 0.03 to 0.9 mass % of Mn as an inevitable impurity, so that the sulfide particles are arranged at a predetermined volume ratio in the sintered body and the sulfide particles are coarsened.
[0008] In Patent Document 2, MnS particles are precipitated in a sintered body by adding MoS2 powder to iron powder containing Mn. Mn is a component that easily oxidizes, and it is difficult to manufacture and obtain raw materials for Mn-rich iron alloys. An object of one embodiment of the present invention is to provide an iron-based sintered sliding member having excellent sliding performance. [Means for solving the problem]
[0009] One embodiment of the present invention is as follows. [1] An iron-based sintered sliding member comprising, by mass%, 3-15% S, 0.2-6% in total of one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg, and the balance being Fe and unavoidable impurities, the member comprising a matrix in which sulfide particles having one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg are dispersed, and pores. [2] The iron-based sintered sliding member according to [1], further comprising Ni: 0 to 10%. [3] The iron-based sintered sliding member according to [1] or [2], further comprising Mo: 0 to 10%. [4] The iron-based sintered sliding member according to any one of [1] to [3], further comprising 0 to 1% of graphite. [5] A sliding part using the iron-based sintered sliding member according to any one of [1] to [4].
[0010] [6] A method for producing an iron-based sintered sliding member, comprising the steps of: adding an iron alloy powder A containing at least one element selected from the group consisting of Cr, Ca, V, Ti, and Mg in a total amount of at least 1 mass%; and adding a sulfur alloy powder B so that the sulfur content of a final sintered body is 3 to 15 mass%; compressing the resulting mixed powder; and sintering the resulting compact at a temperature in the range of 900°C to 1200°C. [7] The method for producing an iron-based sintered sliding member according to [6], wherein the mixed powder further contains at least one type selected from the group consisting of nickel powder and nickel-iron alloy powder in an amount of at least 3 mass %. [8] The method for producing an iron-based sintered sliding member according to [6] or [7], wherein the mixed powder further contains 0 to 1 mass % of graphite.
[0011] [9] The area ratio of metal sulfides is 20% or more, and the number of metal sulfide particles per unit area is 8.0 × 10 10 pieces / m 2 The iron-based sintered sliding member is as described above.
[10] The iron-based sintered sliding member according to [9], wherein the number of metal sulfide particles having a particle diameter of 1 μm or less is 40% or more of the total number of metal sulfide particles.
[11] An iron-based sintered sliding component, in which the area ratio of metal sulfide is 20% or more, and the number of metal sulfide particles having a particle diameter of 1 μm or less is 40% or more relative to the total number of metal sulfide particles.
[12] The iron-based sintered sliding member according to any one of [9] to
[11] , wherein the metal sulfide comprises at least one selected from the group consisting of CrS, CaS, VS, TiS, and MgS.
[13] A sliding part using the iron-based sintered sliding member according to any one of [9] to
[12] . Effect of the Invention
[0012] According to one embodiment, it is possible to provide an iron-based sintered sliding member having excellent sliding performance. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a graph showing the thrust sliding performance of the embodiment. [Diagram 2] FIG. 2 is a graph showing the radial sliding performance of the examples. [Diagram 3] FIG. 3 shows a cross-sectional image of the sintered member of Example 1. [Figure 4] FIG. 4 shows cross-sectional images of the sintered members of Example 1 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, one embodiment of the present invention will be described, but the present invention is not limited to the following examples.
[0015] An iron-based sintered sliding member according to one embodiment is characterized in that it contains, in mass%, 3-15% S, 0.2-6% in total of one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg, and the balance being Fe and unavoidable impurities, and contains a matrix in which sulfide particles having one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg are dispersed, and pores.
[0016] The iron-based sintered sliding member according to one embodiment is made of an iron-based sintered body. The iron-based sintered body contains Fe as a main component. Here, the main component means a component that occupies the majority of the iron-based sintered body. The amount of Fe is preferably 50 mass% or more, more preferably 60 mass% or more, based on the total composition of the iron-based sintered body. The iron-based sintered body can be manufactured by powder metallurgy using raw materials including iron powder and / or iron alloy powder. The porosity of the sintered body is preferably 5 to 40%, and the pores can be impregnated with a lubricating oil.
[0017] The sliding part according to one embodiment is formed using an iron-based sintered sliding material. The sliding part may be integrally formed of an iron-based sintered body. When the sliding part is used by combining an iron-based sintered body with another member, it is preferable that at least a portion including a sliding surface is formed of an iron-based sintered body.
[0018] The iron-based sintered body preferably has a matrix containing a metal sulfide. Examples of the metal sulfide include FeS, MnS, CrS, MoS2, VS, and the like, or a combination thereof. Preferably, the metal sulfide includes one or more selected from the group consisting of MnS, CrS, and VS. More preferably, the metal sulfide includes at least one of CrS and VS. Among them, it is preferable that the iron-based sintered body contains CrS. CrS is blended into the iron-based sintered body originating from Cr in the raw material, and when Cr is contained in the raw material iron powder, CrS is blended and finely distributed in the matrix of the iron-based sintered body, which is a sintered body.
[0019] Metal sulfides contribute to sliding characteristics as solid lubricants. In iron-based sintered bodies, the area ratio of metal sulfides to the matrix is preferably 20% or more. This allows an appropriate amount of metal sulfide to be exposed on the sliding surface of the sliding member, further improving the sliding performance. In the iron-based sintered body, the area ratio of the metal sulfide to the matrix is preferably 35% or less.
[0020] Here, the area ratio of metal sulfides can be measured, for example, by cutting the iron-based sintered body at an arbitrary point, corroding an arbitrary part of the cross section with methanol, mirror-polishing it, processing it so that the metal structure can be seen, and obtaining an elemental analysis image of the processed cross section with an electron beam microanalyzer (for example, "EPMA1600" manufactured by Shimadzu Corporation). The measurement is performed using a wavelength dispersive spectrometer (WDS) method. The measurement conditions can be, for example, an acceleration voltage of 15 kV, a sample current of 100 nA, a measuring time of 5 m·sec, and an area size of 604 × 454 μm. The elemental analysis image can be, for example, an image with a magnification of 500 times. Metal sulfides are observed as black particles in the matrix. For image analysis, for example, image analysis software (WinROOF manufactured by Mitani Shoji Co., Ltd.) can be used.
[0021] The iron-based sintered body preferably has 500 or more metal sulfide particles within an area of 84.4 μm×60.5 μm. This allows the matrix of the iron-based sintered body to contain a larger number of fine metal sulfide particles, making it possible to expose a large number of fine particles on the sliding surface of the sliding member, thereby further improving the sliding performance.
[0022] Here, the number of metal sulfide particles can be determined, for example, by cutting the iron-based sintered body, mirror-polishing the cross section, observing the image of the polished surface, and measuring the number of metal sulfide particles contained in an area of 84.4 μm × 60.5 μm on the polished surface. For image analysis, for example, image analysis software (WinROOF manufactured by Mitani Shoji Co., Ltd.) can be used.
[0023] It is preferable that the metal sulfide is finely dispersed. The iron-based sintered body has a metal sulfide particle count of 8.0×10 per unit area. 10 pieces / m 2 More than 1.0×0 is preferable. 11 pieces / m 2 The above is more preferable. This allows the matrix of the iron-based sintered body to contain a larger number of fine metal sulfide particles, making it possible to expose a large number of fine particles on the sliding surface of the sliding member, thereby further improving the sliding performance. The iron-based sintered body has a metal sulfide particle count of 1.0×10 12 pieces / m 2 The following is preferred: If the number of metal sulfide particles is large, there is a possibility that a plurality of metal sulfides will combine to generate larger particles, so within this range, it is possible to appropriately include a large number of fine particles.
[0024] Here, the number of metal sulfide particles per unit area can be obtained, for example, by cutting the iron-based sintered body, mirror-polishing the cross section, observing the image of the polished surface, and measuring the number of metal sulfide particles contained in a predetermined measurement area of the polished surface. For image analysis, for example, image analysis software (WinROOF manufactured by Mitani Shoji Co., Ltd.) can be used.
[0025] In the iron-based sintered body, the number of metal sulfide particles having a particle size of 1 μm or less is preferably 40% or more, more preferably 50% or more, of the total number of metal sulfide particles. This allows the matrix of the iron-based sintered body to contain a larger number of fine metal sulfide particles, making it possible to expose a large number of fine particles on the sliding surface of the sliding member, thereby further improving the sliding performance. In the iron-based sintered body, the number of metal sulfide particles having a particle diameter of 1 μm or less with respect to the total number of metal sulfide particles may be 100%, but since there is a possibility that coarse particles are mixed in, it may be 90% or less. Within this range, a larger amount of fine particles can be contained more appropriately.
[0026] Here, the ratio of the number of metal sulfide particles having a particle diameter of 1 μm or less can be obtained by, for example, cutting an iron-based sintered body, mirror-polishing the cross section, observing an image of the polished surface, measuring the number of all metal sulfide particles contained in an area of any size of 84.4 μm×60.5 μm on the polished surface, and measuring the number of metal sulfide particles having a particle diameter of 1 μm or less, and then calculating the ratio of the numbers. For example, image analysis software (WinROOF manufactured by Mitani Shoji Co., Ltd.) can be used for the image analysis.
[0027] The iron-based sintered body preferably contains, in mass %, S: 3-15%, one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg: a total amount of 0.2-6%, and the balance: Fe and unavoidable impurities. Furthermore, the iron-based sintered body can further contain Ni: 0 to 10%, Mo: 0 to 10%, graphite: 0 to 1%, or a combination thereof.
[0028] The composition of the iron-based sintered body will be described below. S: 3-15% By including S in the iron-based sintered body, it is possible to include metal sulfide in the matrix. This allows an appropriate amount of metal sulfide to be exposed on the sliding surface of the sliding member, and the sliding performance can be further improved. S is preferably 0.5% or more, more preferably 1% or more, even more preferably 2% or more, and even more preferably 3% or more. Excessive S can inhibit sinterability and reduce strength. In addition, S can also scatter during sintering. Therefore, S is preferably 15% or less, more preferably 6% or less, more preferably 5% or less, and even more preferably 4% or less. In addition, within this range, it is possible to prevent multiple metal sulfide particles from bonding together to form a single large particle, and finer metal sulfide particles can be contained in the matrix, thereby further improving the sliding performance. The sulfur is preferably added as an unstable sulfur alloy powder, such as iron sulfide or MoS2.
[0029] Cr: 0.2~6% Usually, the greater the difference in electronegativity between S and the metal, the greater the ease of sulfide formation. The electronegativity values (Pauling electronegativity) are S: 2.58, Mn: 1.55, Cr: 1.66, Fe: 1.83, Cu: 1.90, Ni: 1.91, and Mo: 2.16, so the order of ease of sulfide formation is Mn>Cr>Fe>Cu>Ni>Mo. For this reason, sulfur combines with a trace amount of Mn contained as an impurity in the iron powder to generate MnS. Then, a reaction occurs with chromium, and chromium sulfide precipitates. Chromium has a high melting point, does not aggregate, and reacts with sulfur while remaining in a dispersed state, so fine metal sulfides can be generated in the matrix. By making Cr 0.2% or more, preferably 0.5% or more, and more preferably 1.0% or more, the material strength can be increased and the sliding performance can be improved. It is preferable that Cr is 6% or less.
[0030] Ca, V, Ti, and Mg also cause the same phenomenon as Cr, and can generate fine metal sulfides in the matrix. Ca, V, Ti, and Mg are each independently preferably 0.1 to 6.0%, more preferably 0.2 to 6%, and even more preferably 0.2 to 4%. The total amount of Cr, Ca, V, Ti, and Mg is preferably 0.2 to 6%, and more preferably 0.2 to 4%.
[0031] Mn: 0-0.5% Mn is present in iron powder as an inevitable impurity. Mn is also an easily oxidized component, so it is difficult to produce a manganese-rich iron-manganese alloy. Even if manganese-rich iron-manganese alloys exist, they are expensive. Mn can generate fine metal sulfides in the matrix, but there is an upper limit to the amount of manganese in the raw material powder of the iron-manganese alloy that provides the manganese, and there is also an upper limit to the amount of metal sulfides that can be formed in the sintered body. The Mn content is preferably 0 to 0.5%.
[0032] Mo: 0-10% Mo has the effect of promoting sintering, stabilizing the metal structure, especially the ferrite phase, and resulting in a sintered body with high strength. Mo is preferably 0.1% or more, more preferably 1% or more, to increase the material strength and improve the sliding performance. Mo is preferably 10% or less. Mo can be added as Mo powder and / or Mo alloy powder.
[0033] Ni: 0-10% Ni improves the hardenability of iron-based sintered bodies, and after sintering and cooling, it has the effect of including a hardened structure in the iron-based sintered body and remaining as austenite. In addition, due to the relationship of electronegativity, Ni does not inhibit the formation of metal sulfides mainly composed of iron sulfide. When used in combination with C, Ni improves the hardenability of the iron matrix, making pearlite finer and increasing strength, and makes it easier to obtain high-strength bainite and martensite at normal cooling rates during sintering. Ni content of 0.1% or more, preferably 0.5% or more, more preferably 1.0% or more can increase the material strength and improve the sliding performance. Ni content is preferably 10% or less, more preferably 8% or less. Ni can be added as Ni powder and / or Ni alloy powder.
[0034] C: 0-1% C is not an essential element, but when added in an amount of 0 to 1%, a part of C dissolves in Fe, thereby improving the strength.
[0035] The iron-based sintered material is composed of the remainder Fe and may contain unavoidable impurities. The iron-based sintered material may further include one or more additives selected from the group consisting of minerals, oxides, nitrides, and borides that do not diffuse into the matrix. These additives include, for example, MgO, SiO2, TiN, CaAlSiO3, CrB2, etc., or combinations thereof.
[0036] The matrix of the iron-based sintered material preferably contains, as a metal structure, at least one selected from the group consisting of ferrite, pearlite, and martensite, and more preferably has a metal structure in which ferrite is the main component. The matrix preferably has the metal sulfide dispersed therein, and more preferably has the metal sulfide finely dispersed therein.
[0037] Hereinafter, a method for producing an iron-based sintered sliding member will be described, however, the iron-based sintered sliding member according to one embodiment is not limited to the one produced by the following production method. A manufacturing method of an iron-based sintered sliding member according to one embodiment is a method in which sulfur alloy powder B is added to iron alloy powder A containing at least one kind selected from the group consisting of Cr, Ca, V, Ti, and Mg in a total amount of at least 1 mass % so that the sulfur content of the final sintered body is 3 to 15 mass %, the resulting mixed powder is compression molded, and the resulting molded body is sintered at a temperature range of 900°C to 1200°C.
[0038] Cr, Ca, V, Ti, and Mg are each preferably independently contained in an amount of 0.1 to 8 mass% based on the total amount of the iron alloy powder. The total amount of Cr, Ca, V, Ti, and Mg is preferably 1 mass% or more based on the total amount of the iron alloy powder. In addition, it is preferable that the sulfur alloy powder is added to the mixed powder so that the sulfur content of the final sintered body is 3 to 15 mass%. When iron sulfide is used as the sulfur alloy powder, iron sulfide containing 35 mass% or more of S is preferable.
[0039] According to this manufacturing method, the iron alloy powder A and the sulfur alloy powder B serving as a source of S are added separately to the raw material powder, so that S released by decomposition of the sulfur alloy powder during sintering can be combined with one or more elements selected from the group consisting of Cr, Ca, V, Ti, and Mg in the matrix to precipitate MnS, CrS, VS, or a combination thereof. According to this manufacturing method, MnS, CrS, VS, or a combination thereof can be precipitated in the form of fine particles within the crystal grains.
[0040] The green compact is preferably sintered at a maximum holding temperature of 900°C to 1200°C. By keeping the temperature within this range, the sulfur alloy powder decomposes, and S bonds with one or more elements selected from the group consisting of Cr, Ca, V, Ti, and Mg in the matrix to form fine metal sulfides. In addition, the diffusion of C, Ni, Mn, Cr, Cu, Mo, V, etc. into Fe is promoted, and a metal structure with high matrix hardness is generated, and the tensile strength of the iron-based sintered body can be further increased. The green compact is preferably held at the maximum holding temperature for 10 to 90 minutes.
[0041] In addition, if a large amount of oxygen is contained in the sintering atmosphere, S decomposed from metal sulfides will combine with oxygen to produce SO X Sintering is preferably performed in a vacuum atmosphere or a non-oxidizing atmosphere, since the amount of S that is released as a gas and bonds with the base metal is reduced. Examples of non-oxidizing atmospheres that can be used include decomposed ammonia gas, nitrogen gas, hydrogen gas, argon gas, etc., with a dew point of -10°C or less.
[0042] After sintering, the sintered body is preferably cooled at a cooling rate of 2° C. / min to 400° C. / min, more preferably 5 to 150° C. At this cooling rate, it is preferable to cool the body in a temperature range from the maximum holding temperature to 900 to 200° C.
[0043] The iron alloy powder preferably contains, in addition to the main component Fe, one or more elements selected from the group consisting of Cr, Ca, V, Ti, and Mg. The total amount of the one or more elements selected from the group consisting of Cr, Ca, V, Ti, and Mg is preferably 1 mass% or more based on the total amount of the iron powder. The iron alloy powder may further contain C, Ni, Cu, Mo, or a combination thereof. It is preferable to adjust the blending amount of these elements so as to satisfy the range of the overall composition of the iron-based sintered body described above.
[0044] S is preferably added as a sulfur alloy powder, for example, iron sulfide powder, molybdenum disulfide powder, or the like. Although S has a weak compounding power at room temperature, it is highly reactive at high temperatures and combines not only with metals but also with nonmetallic elements such as H, O, and C. In the manufacture of sintered bodies, a molding lubricant is generally added to the raw material powder, and the molding lubricant is volatilized and removed during the temperature rise process of the sintering process, a process known as dewaxing. If S is added in the form of sulfur powder, it combines with the components (mainly H, O, and C) generated by the decomposition of the molding lubricant and is released, making it difficult to stably provide the S required for forming metal sulfides. If S is added in the form of sulfur alloy powder, it exists in the form of iron sulfide in the temperature range (about 200 to 400 °C) where the dewaxing process is performed, so it does not combine with the components generated by the decomposition of the molding lubricant and S does not release, and therefore the S required for forming metal sulfides can be stably provided.
[0045] When the temperature exceeds 988°C during the sintering process, a eutectic liquid phase of the sulfur alloy is generated, resulting in liquid phase sintering, which promotes the growth of necks between powder particles. In addition, S diffuses uniformly from this eutectic liquid phase into the iron matrix, allowing metal sulfide particles to be more uniformly dispersed and precipitated in the matrix. In addition, by including one or more elements selected from the group consisting of Cr, Ca, V, Ti, and Mg in the raw iron alloy powder, these elements in the matrix react with S to produce finer metal sulfides.
[0046] The raw material powder mixture may further include nickel powder, nickel-iron alloy powder, or a combination thereof. Nickel is preferably used because it dissolves as Ni in the matrix of the iron-based sintered body and acts to increase the strength of the matrix. Nickel may be added as a single substance or as an alloy. Nickel can be added so that it is 3% by mass or more, preferably 5% by mass or more, based on the total amount of the mixed powder.
[0047] The mixed powder may further contain 0 to 1 mass % of graphite. The mixed powder may further contain 0 to 10 mass % of Mo. The mixed powder may further contain an optional component such as a die lubricant.
[0048] Other embodiments of the iron-based sintered sliding member will be described below. In another embodiment of the iron-based sintered sliding member, the area ratio of the metal sulfide is 20% or more, and the number of metal sulfide particles per unit area is 8.0×10 10 pieces / m 2 The present invention is characterized in that: The iron-based sintered sliding member according to another embodiment is characterized in that the area ratio of the metal sulfide is 20% or more, and the number of metal sulfide particles having a particle diameter of 1 μm or less is 40% or more relative to the total number of metal sulfide particles. According to this, the iron-based sintered body can be used to improve the sliding performance of the sliding member.
[0049] In the iron-based sintered sliding member according to the above-mentioned other embodiment, the area ratio of the sulfide is large, and the number of sulfide particles per unit area is large, so that the metal sulfide contained in the matrix becomes fine, and the sliding performance can be improved. In the iron-based sintered sliding member according to the above-mentioned further embodiment, the area ratio of the sulfides is large, and the ratio of the particle diameter of the metal sulfides having a particle diameter of 1 μm or less is high, so that the metal sulfides contained in the matrix become fine, and the sliding performance can be improved.
[0050] The iron-based sintered body according to the above-mentioned embodiment preferably includes pores derived from raw materials such as iron powder, together with a matrix containing metal sulfide. When a lubricant is applied to the sliding member for use, the lubricant is retained by the pores, and the sliding performance can be improved over a long period of time.
[0051] The iron-based sintered sliding member according to the above-mentioned embodiment can be formed by adding sulfur alloy powder to iron alloy powder containing one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg, compressing and molding the obtained mixed powder, and sintering the obtained molded body, thereby dispersing metal sulfide finely in the crystals of the sintered body. EXAMPLES
[0052] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0053] "Manufacturing Example 1" Example 1 Raw material powder A: Iron alloy powder with 3% Cr, 0.5% Mo, 0.5% V, and the balance iron by mass. Raw material powder B: Iron sulfide with a mass ratio of 35% S Raw material powder C Ni powder A raw material powder was obtained by mixing 10% by mass of powder B, 5% by mass of powder C, and the remainder being powder A. The raw material powder was then molded under a molding pressure of 600 MPa to produce a ring-shaped green compact, which was then sintered at 1130° C. in a non-oxidizing gas atmosphere to produce the sintered member of Example 1.
[0054] The sintered components were cut and the chemical composition of the matrix of the cross section was analyzed. The results are shown in Table 1.
[0055] The area ratio of the metal sulfide in the sintered component was determined by cutting the obtained sample, mirror-polishing the cross section, observing the cross section, and measuring the area of the matrix excluding pores and the area of the metal sulfide using image analysis software (WinROOF, manufactured by Mitani Shoji Co., Ltd.), and calculating the area (%) of the metal sulfide in the matrix area. The measurement area was 84.4 μm × 60.5 μm. When the cross section was observed, the metal sulfides were observed as black particles in the matrix. The number of metal sulfide particles in the 84.4 μm × 60.5 μm region was determined by observing and analyzing the image of the cross section of the sintered member in the same manner as the above area ratio, and the number of metal particles per unit area was calculated. The number of metal sulfide particles having a particle size of 1 μm or less relative to the total number of metal sulfide particles was determined by observing and analyzing images of the cross section of the sintered member in the same manner as for the above area ratio. The maximum particle diameter of each metal sulfide particle was measured by calculating the area of each particle and converting it into the diameter of a circle equal to this area. In addition, when multiple metal sulfide particles were bonded together, the bonded metal sulfides were treated as a single metal sulfide, and the equivalent circle diameter was calculated from the area of this metal sulfide. The results are shown in Table 2.
[0056] Comparative Example 1 A ring-shaped green compact was produced in the same manner as in Example 1, except that a mixed powder named LBC3 according to the JIS standard was used, and sintered at 800° C. in a non-oxidizing gas atmosphere to produce a sintered member of Comparative Example 1. The chemical composition of the matrix of the sintered member was measured in the same manner as in Example 1. The results are shown in Table 1.
[0057] [Table 1]
[0058] [Table 2]
[0059] (evaluation) Sintered components having the following dimensions were produced in the same manner as above, and the following evaluations were carried out. "Thrust sliding performance" A disk-shaped sintered member having a diameter of 35 mm and a thickness of 5 mm was prepared. A ring-shaped mating material made by FSD with an outer diameter of 25 mm, an inner diameter of 24 mm, and a thickness of 15 mm was prepared. A sliding test was carried out using a ring-on-disk friction and wear tester under the following conditions to measure the friction coefficient. Circumferential speed: 0.5m / sec Surface pressure: 1,2,...,20MPa Time: 5 minutes at each pressure Oil type: Oil VG460 (drop)
[0060] In addition, the wear amount (μm) of the disk and ring (FCD) was measured before and after the test. The results are shown in Figure 1. As can be seen from Figure 1, the sintered member of Example 1 had a friction coefficient that was equal to or lower than that of Comparative Example 1, and the sliding performance was improved. In addition, by using the sintered member of Example 1, the amount of wear of the mating material as well as the sintered member could be reduced.
[0061] "Radial sliding performance" A ring-shaped sintered member having an outer diameter of 16 mm, an inner diameter of 10 mm, and a thickness of 10 mm was prepared. A shaft made of S45C with a diameter of 9.980 mm and a length of 80 mm was prepared. A radial compression test was carried out under the following conditions to measure the coefficient of friction. Circumferential speed: 1.57m / min Surface pressure: 1, 2,..., 80MPa Time: 5 minutes at each pressure Oil type: Oil VG460 (impregnation)
[0062] In addition, the amount of wear (μm) of the ring was measured before and after the test. The results are shown in Figure 2. As can be seen from Figure 2, the sintered member of Example 1 had a friction coefficient that was equal to or lower than that of Comparative Example 1, and the sliding performance was improved. In addition, by using the sintered member of Example 1, the amount of wear of the sintered member could be reduced.
[0063] 3 shows the metal structure (mirror polished) of the sintered member of Example 1. The iron matrix is the white part, the metal sulfide particles are the grey parts, and the pores are the black parts. From FIG. 3, it can be seen that metal sulfide particles (gray) are precipitated and finely dispersed in the iron matrix (white).
[0064] Comparative Example 2 A raw material powder was obtained by mixing the raw materials so as to obtain the chemical composition shown in Table 1. In the same manner as in Example 1, a ring-shaped green compact was produced and sintered at 1130°C in a non-oxidizing gas atmosphere to produce a sintered member of Comparative Example 2. The chemical composition and physical properties of the matrix of the sintered member were measured in the same manner as in Example 1. The results are shown in Tables 1 and 2.
[0065] 4 shows a comparison of the metal structures (mirror polished) of the sintered members of Example 1 and Comparative Example 2. The iron matrix is the white part, the metal sulfide particles are the grey parts, and the pores are the black parts. It can be seen from FIG. 4 that, compared to Comparative Example 2, the metal sulfide particles (gray) of Example 1 are precipitated and finely dispersed in the iron matrix (white).
[0066] "Manufacturing Example 2" The raw material powders shown in Table 3 were prepared. The raw material powders shown in Table 3 were mixed in the combinations shown in Table 4. The blending ratio of each raw material powder was adjusted so that the matrix composition shown in Table 4 was obtained. A green compact was produced in the same manner as in Production Example 1 above, and a sintered member was produced using this. In Example 10, a sintered member was produced in the same manner as in Comparative Example 1 above, using a mixed powder called LBC3 according to the JIS standard.
[0067] For the sintered component, the area ratio of metal sulfide, the number of metal sulfide particles per unit area, and the number of metal sulfide particles with a particle diameter of 1 μm or less relative to the total number of metal sulfide particles were measured in the same manner as in Production Example 1 above. The thrust sliding performance and radial sliding performance of the sintered members were evaluated in the same manner as in Production Example 1. In the evaluation of thrust sliding performance, the thrust wear amount (μm) was calculated from the wear amount of the disk before and after the test. In the evaluation of radial sliding performance, the radial wear amount (μm) was calculated from the wear amount of the ring before and after the test. The results are shown in Table 5.
[0068] [Table 3]
[0069] [Table 4]
[0070] [Table 5]
Claims
1. A composition including the metal sulfide, the composition including the metal sulfide being, in mass%, 3-15% S, 0.2-6% in total of one or more selected from the group consisting of Cr, Ca, V, Ti, and Mg, and the balance being Fe and unavoidable impurities; and a matrix including pores, the metal sulfide including particles of the metal sulfide dispersed within crystal grains of the matrix, The iron-based sintered sliding member has an area ratio of 20% or more, and the number of metal sulfide particles having a particle diameter of 1 μm or less is 40% or more of the total number of metal sulfide particles.
2. 2. The iron-based sintered sliding member according to claim 1, wherein the matrix further contains Ni: 0 to 10%.
3. 3. The iron-based sintered sliding member according to claim 1, wherein the matrix further contains Mo: 0 to 10%.
4. The iron-based sintered sliding member according to any one of claims 1 to 3, wherein the matrix further contains 0 to 1% graphite.
5. A sliding part using the iron-based sintered sliding member according to any one of claims 1 to 4.
6. 5. The method for producing an iron-based sintered sliding member according to claim 1, further comprising adding sulfur alloy powder B to iron alloy powder A containing at least one element selected from the group consisting of Cr, Ca, V, Ti, and Mg in a total amount of at least 1 mass % so that the sulfur content of a final sintered body is 3 to 15 mass %, compressing the resulting mixed powder, and sintering the resulting compact in a temperature range of 900°C to 1200°C.
7. 7. The method for producing an iron-based sintered sliding member according to claim 6, wherein the mixed powder further contains at least one kind selected from the group consisting of nickel powder and nickel-iron alloy powder in an amount of at least 3 mass %.
8. The method for producing an iron-based sintered sliding member according to claim 6 or 7, wherein the mixed powder further contains 0 to 1 mass % of graphite.
9. The number of metal sulfide particles per unit area is 8.0 x 10 10 pieces / m 2 The iron-based sintered sliding member according to any one of claims 1 to 4, wherein
10. 5. The iron-based sintered sliding member according to claim 1, wherein the number of metal sulfide particles having a particle diameter of 1 μm or less is 50% or more of the total number of said metal sulfide particles.
11. 5. The iron-based sintered sliding member according to claim 1, wherein the number of metal sulfide particles having a particle diameter of 1 μm or less is 50% or more of the total number of said metal sulfide particles.
12. The iron-based sintered sliding member according to claim 1 , wherein the metal sulfide includes CrS.
13. A sliding part using the iron-based sintered sliding member according to any one of claims 9 to 12.
Citation Information
Patent Citations
Ring of spinning and weaving machinery made of sintered iron alloy
JP1982188653A
Free cutting sintered member and production method therefor
JP2002332552A
Method for producing valve seat for check valve
JP2006219699A
Sintered valve seat and method for producing the same
JP2007113101A
Iron-based sintered sliding member and production method thereof
JP2014181381A
